Weighted Bilinear Interpolation Based Generic Multispectral Image Demosaicking Method - Gupta, Medha; Ram, Mangey (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*327.77px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.961133);" role="presentation">Multispectral imag<span dir="ltr" style="left: calc(var(--scale-factor)*149.18px); top: calc(var(--scale-factor)*327.77px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938339);" role="presentation">ing systems acquire images having more than three spectral bands and these images play <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*340.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00622);" role="presentation">crucial role in various <span dir="ltr" style="left: calc(var(--scale-factor)*171.05px); top: calc(var(--scale-factor)*340.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946636);" role="presentation">applications such as remote <span dir="ltr" style="left: calc(var(--scale-factor)*292.87px); top: calc(var(--scale-factor)*340.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.871826);" role="presentation">sensing, <span dir="ltr" style="left: calc(var(--scale-factor)*330.19px); top: calc(var(--scale-factor)*340.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.986214);" role="presentation">medical imaging, military surveillance, vision <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*354.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.997208);" role="presentation">inspection for food quality control, <span dir="ltr" style="left: calc(var(--scale-factor)*224.93px); top: calc(var(--scale-factor)*354.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933949);" role="presentation">archaeological surveys e<span dir="ltr" style="left: calc(var(--scale-factor)*327.43px); top: calc(var(--scale-factor)*354.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01928);" role="presentation">tc. But <span dir="ltr" style="left: calc(var(--scale-factor)*360.91px); top: calc(var(--scale-factor)*354.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.987716);" role="presentation">the high cost of multispectral <span dir="ltr" style="left: calc(var(--scale-factor)*490.42px); top: calc(var(--scale-factor)*354.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939747);" role="presentation">imaging <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*367.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.864581);" role="presentation">systems <span dir="ltr" style="left: calc(var(--scale-factor)*106.94px); top: calc(var(--scale-factor)*367.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954391);" role="presentation">limit their usage. <span dir="ltr" style="left: calc(var(--scale-factor)*179.69px); top: calc(var(--scale-factor)*367.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964454);" role="presentation">Similar to the use of color-<span dir="ltr" style="left: calc(var(--scale-factor)*291.67px); top: calc(var(--scale-factor)*367.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.03569);" role="presentation">filter-<span dir="ltr" style="left: calc(var(--scale-factor)*314.47px); top: calc(var(--scale-factor)*367.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94852);" role="presentation">array interpolation methods in development of low <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*380.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.985177);" role="presentation">cost RGB color cameras, researchers have been exploring the use of multispectral image demosaicking <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*393.91px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918393);" role="presentation">technologies for <span dir="ltr" style="left: calc(var(--scale-factor)*139.22px); top: calc(var(--scale-factor)*393.91px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922494);" role="presentation">developing affordable multispectral imaging systems. I<span dir="ltr" style="left: calc(var(--scale-factor)*360.07px); top: calc(var(--scale-factor)*393.91px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.898864);" role="presentation">n this paper, we present a generic simple <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*407.11px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941072);" role="presentation">weighted bilinear interpolation based multi<span dir="ltr" style="left: calc(var(--scale-factor)*246.89px); top: calc(var(--scale-factor)*407.11px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929533);" role="presentation">spectral i<span dir="ltr" style="left: calc(var(--scale-factor)*284.11px); top: calc(var(--scale-factor)*407.11px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929786);" role="presentation">mage demosaicking method. This method is applicable for <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*420.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927356);" role="presentation">any number of spectral bands image, however it critically depends upon the multispectral filter array tha<span dir="ltr" style="left: calc(var(--scale-factor)*494.74px); top: calc(var(--scale-factor)*420.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.870433);" role="presentation">t needs <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*433.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9975);" role="presentation">to be carefully designed for the weighted bilinear method to be easily applicable. We use two publically <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*446.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942608);" role="presentation">available multispectral image datasets for the performance evaluation of the proposed approach and present <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*460.03px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.861074);" role="presentation">some <span dir="ltr" style="left: calc(var(--scale-factor)*95.54px); top: calc(var(--scale-factor)*460.03px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919501);" role="presentation">interesting <span dir="ltr" style="left: calc(var(--scale-factor)*140.30px); top: calc(var(--scale-factor)*460.03px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931318);" role="presentation">insights derived fr<span dir="ltr" style="left: calc(var(--scale-factor)*213.17px); top: calc(var(--scale-factor)*460.03px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903913);" role="presentation">om the experimental results